1990s – Decade of Change - Wilson, Ross (Victoria University of Wellington Law Review, 2003)
This paper provides a trade union perspective on the changes to New Zealand accident compensation laws during the 1990s, in the context of the political, social and economic environment of the time, and measures those changes, including the changing structure of the statutory scheme and its delivery, against the original Woodhouse Commission principles of Community Responsibility, Comprehensive Entitlement, Real Compensation, Complete Rehabilitation, and Administrative Efficiency.